Case Report: Cavernous Sinus Syndrome as the Initial Presentation of Multiple Myeloma - Silverman, Rebecca F.; Hanson, Lawrence; Salahi, Navid; Li, Zhonghua; Boruk, Marina; Hodgson, Nickisa M. (Frontiers in Ophthalmology, 2022)
Multiple myeloma is the second most common hematologic malignancy. Ocular manifestations of multiple myeloma are extremely rare and may be the first presentation leading to diagnosis. Ophthalmologists routinely encounter cavernous sinus syndrome and there are a wide range of possible etiologies. Here, we present a case of a patient presenting with diplopia, ptosis, and ophthalmoplegia found to have a suprasellar plasmacytoma with systemic work up consistent with multiple myeloma. Multiple myeloma is a rare cause of cavernous sinus syndrome and should be considered in the setting of a skull base mass.